EFFECTS OF SILVER NANOPARTICLES ON THYROID GLAND STRUCTURE AND FUNCTION IN FEMALE RATS - Sulaiman, Amal A; M Luaibi, Noori; A Qassim, Hiba (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Due to their unique properties, silver nanoparticles (AgNPs) gained a broad utilization in nano-based industries and medicine, which may expose human to increased levels of NPs. However, little is known about their potential harmful effects on endocrine physiology. Hence, this study aimed to investigate the potential dose- and time-dependent outcomes of AgNPs on serum levels of thyroid hormones and thyroid gland histology in female rats. Methods: A total of 60 female rats were divided into three groups (each of 20 animals), treated with AgNPs for (10, 20, and 30) days. Within each treatment period, animals were assigned into four subgroups each of five rats; control treated with vehicle and the others treated with 12.5, 25, and 50 mg/kg of AgNPs, respectively, by intraperitoneal injection. At the end of treatments, all rats were sacrificed; blood samples were obtained and analyzed for serum levels of T3, T4, and thyroid-stimulating hormone (TSH). Thyroid gland was removed and weighed then kept in buffered formalin solution for microscopic examination. Results: The data showed a significant increase in the weight of the thyroid gland after 20 and 30 days of the treatment with 50 mg/kg of AgNPs, while the 25 mg/kg dose of AgNps resulted in significant increase only after 30 days. Serum levels of T3 and TSH were nonsignificantly altered by AgNPs in all the treatment groups. Thyroxin levels (T4) were significantly decreased after long-term exposure. Histological specimens of AgNPs treated group showed disturbance of the normal architecture of the thyroid tissue with degeneration of thyroid follicles and desquamated luminal cells. Conclusion: The results of the current study suggested the possible disrupting potential of long-term exposure to high level of AgNPs on thyroid gland function and histology in female rats.